Endoscopic antrostomy in the treatment of odontogenic maxillary sinusitis – two cases report - Dimić, Aleksandar; Brković, Božidar; Erdoglija, Milan; Grgurević, Uglješa; Sotirović, Jelena; Rašić, Dejan (Vojnosanitetski pregled, 2021)
Introduction. Maxillary sinusistis of odontogenic origin is a well-known condition that occurs due to close relationship of the maxillary posterior teeth to the maxillary sinus. We presented two patients with symptoms and signs of chronic inflammation of the maxillary sinus of odontogenic origin. Case report. In both patients, after clinical examination, microbiological testing, skin prick tests to inhalant allergens, and endoscopy of the nasal cavity, we performed the cone beam computed tomography (CBCT) of paranasal sinuses, which showed thickening of the mucosal lining of the maxillary sinus. The mucosal oedema resulted in obstruction of the osteomeatal complex in both patients. The presence of a foreign body in the right alveolar recess in the first case and in the left osteomeatal complex in the second case were noticed. The both foreign bodies had densities similar to bone. The alveolar recesses in both cases were below the level of the nasal cavity floor. The patients were treated by endoscopic approach, a combination of lower and middle meatal antrostomy. The thickened mucous membrane was removed in the region of the osteomeatal complex, and then the foreign bodies were removed in both cases. Histopathological analysis proved that both foreign bodies were tooth roots. Conclusion. This case report show how be able to successfully surgically remove foreign bodies from the maxillary sinuses using endoscopic approach, a combination of both, lower and middle meatal antrostomy.